Optimized effective strain model for externally bonded FRP shear strengthened RC members - Teo, W. (International Institute for FRP in Construction (IIFC), 2014)
Discrepancies in the current design guidelines on externally bonded FRP shear strengthening for reinforced concrete (RC) structures had initiated this research study. It is generally believed that the erroneous and irrelevant effective FRP strain models adopted in many of the design guidelines, which are derived entirely based on the 45-deg truss analogy, contributes significantly for such discrepancies. Previous research work by the authors had revealed the successful use of truss model optimization to generate a realistic and viable model, and furthermore accurately evaluate the shear strength of FRP strengthened members. The objective of this research is intended to develop a new effective FRP strain model based on this optimized truss model. The model is derived by calibration with the experimental test data collected from existing published literature. The results obtained show a very good correlation between predicted and experimental values. An average shear strength ratio (Vn,exp/Vn,pre) of 1.09 with coefficient of variation (COV) of 14.1 was obtained. The performance of this new optimized effective strain model is very promising and indeed could potentially be recommended into the current design guidelines.